2022
DOI: 10.1007/s00508-021-01999-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of C-reactive protein to albumin ratio in hospitalized coronavirus disease 2019 (COVID-19) patients

Abstract: C‑reactive protein (CRP) and albumin are inflammation sensitive parameters that are regulated by interleukin‑6 inflammatory pathways. The CRP to albumin ratio (CAR) integrates these two into a potent clinical parameter whose clinical and prognostic association in the context of coronavirus disease 2019 (COVID-19) have not been well defined. We aimed to investigate the clinical and prognostic significance of CAR in the context of COVID-19 infection. We retrospectively analyzed 2309 consecutive COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…Higher COVID-19 severity and features of stronger inflammation have been recognized as predictors of VTE in several cohorts ( 30 - 32 ) and in the current study, highlighting the interconnected pathways of hyperinflammation and thrombosis. Lower MCHC is a red blood cell index reflecting hemoglobin content and the quality of erythropoiesis.…”
Section: Discussionsupporting
confidence: 57%
“…Higher COVID-19 severity and features of stronger inflammation have been recognized as predictors of VTE in several cohorts ( 30 - 32 ) and in the current study, highlighting the interconnected pathways of hyperinflammation and thrombosis. Lower MCHC is a red blood cell index reflecting hemoglobin content and the quality of erythropoiesis.…”
Section: Discussionsupporting
confidence: 57%
“…Unfavorable disease course has been especially associated with chronic metabolic comorbidities, such as arterial hypertension, diabetes mellitus, hyperlipoproteinemia, and obesity ( 2 - 7 ). Charlson comorbidity index (CCI), a summary measure of comorbidities validated as a prognostic tool in a number of chronic and malignant diseases ( 8 , 9 ), has also been associated with an adverse COVID-19 clinical course ( 10 - 15 ).…”
mentioning
confidence: 99%
“…Recent studies have confirmed that these biomarkers provide substantive information about clinical deterioration and the risk of mortality [ 25 , 26 , 38–40 ]. In addition, some studies revealed the role of albumin in COVID-19 prognostication reflecting both possible liver damage, inflammation and the nutritional status of patients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%